Penanaman Nilai-Nilai Agama Islam di Lingkungan Sekolah dalam Menumbuhkan Kecerdasan Spiritual Anak - Eko Hadi Wardoyo (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2019)
The planting of Islamic religious values in the school environment is very important, especially for children who have been obliged to carry out the orders of religious law. This study aims to describe the planting of Islamic religious values in the school environment in fostering children's spiritual intelligence. The results of this study can be used to add scientific information about the problem of planting Islamic religious values in the school environment. This research comes from several literature related to the subject matter or referred to as library research. The data analysis technique uses descriptive analysis. The results of the study show that the cultivation of Islamic religious values in the school environment is very supportive to foster children's spiritual intelligence.